Larangan Berperilaku Boros dalam Al-Qur’an dan As-Sunnah - Rozzaq, Abdur; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
Every individual has undoubtedly received a portion of rizq (wealth) granted by Allah. However, sometimes some people unknowingly engage in extravagant spending in inappropriate places. The aim of this research is to explore the concept of “excessive spending” in the Qur’an and Sunnah. The research method used is qualitative, employing literature review and content analysis. This study encompasses discussions on general perspectives regarding wastefulness, verses that address wasteful behavior in the Qur’an and Sunnah, and an analysis of verses and hadiths pertaining to “excessive spending” behavior. The conclusion of this research reveals that forms of wasteful behavior can include excessively splurging on wealth, food, drinks, and other unnecessary items. Scholars offer several pieces of advice and guidance to avoid such wastefulness. This research highlights the importance of refraining from wasteful behavior to prevent negative consequences, including aligning oneself with satan.